The evolution of three-dimensional knee kinematics after ACL reconstruction within one year - Kong, Lingchuang; Lai, Huahao; Zeng, Xiaolong; Gao, Peng; Liang, Wenhao; Gao, Qi; Kong, Zhiyuan; Wu, Wu; Wu, Xiaona; Zhang, Tao (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThis study aims to explore the dynamic changes in the six degrees of freedom (6DOF) kinematics of the knee joint in patients within one year after anterior cruciate ligament reconstruction (ACLR), combined with clinical scoring systems to analyze functional recovery characteristics, providing scientific evidence for optimizing postoperative rehabilitation strategies.MethodsThe study enrolled 49 patients followed up at 3 months postoperatively, 33 patients at 6 months, and 35 patients at 12 months. Twenty-nine healthy controls were recruited. A three-dimensional motion capture system was used to collect 6DOF knee kinematic data at 3, 6, and 12 months after surgery, including flexion-extension, internal-external rotation, adduction-abduction angles, and anterior-posterior, distal-proximal, medial-lateral translation data. Clinical function was assessed using the IKDC and KOOS scores. One Way ANOVA of one-dimensional statistical parametric mapping (SPM1D) was used to assess the changes in gait kinematics and differences compared to healthy controls.ResultsAfter ACLR, the IKDC and KOOS scores of patients significantly improved between 3 and 12 months postoperatively, showing good subjective functional recovery. Over the course of one year, the knee kinematic data of gait has gradually recovered. However, abnormalities in knee joint kinematics still exist. In the coronal plane, the adduction angle of the knee joint during motion is relatively large (p < 0.05); In the sagittal plane, the flexion angle increased during the standing phase (p < 0.05); In the transverse plane, the internal rotation angle of the knee joint increased compared to the controls (p < 0.05). The range of motion of flexion and rotational angles decreased compared to the controls (p < 0.05).DiscussionThe kinematic recovery of the knee joint in ACLR patients presents multidimensional characteristics and dynamic changes. The recovery rates and patterns differ significantly across dimensions, with some abnormalities not fully corrected within one-year post-urgery. These findings provide scientific evidence for individualized rehabilitation strategies, emphasizing the need for strengthening joint stability and range of motion recovery in the early postoperative phase (0-6 months) and focusing on correcting rotational and flexion-extension function during the later phase (6-12 months) to further improve knee function and prevent long-term adverse outcomes.